2015
DOI: 10.1071/sh14144
|View full text |Cite
|
Sign up to set email alerts
|

Paying the price in an era of HIV treatment as prevention: a retrospective study of the cost burden of HIV treatment for people living with HIV in Victoria, Australia

Abstract: There may be meaningful patient costs associated with accessing ART for some PLWH. New HIV treatment-based prevention strategies need to consider financial vulnerabilities and appropriately targeted initiatives to alleviate patient costs associated with ART, ensuring they do not act as a barrier to commencement of and adherence to HIV treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Within the specific context of HIV patients, these financial considerations can substantially influence their ability to avail themselves of vital medical care, procure prescribed medications and participate in routine medical assessments, thereby contributing to variations in their healthcare service avoidance behaviours. Our findings align with prior research conducted in both developed and developing countries, including instances such as Australia and Cameroon, where budgetary constraints have been identified as a hindrance to healthcare-seeking behaviours 21 22. A study conducted in Vietnam indicated that there were 73.3% of participants reported that they were able and willing to pay for HIV treatment expenditures, unlike the low individual willingness to pay rate recorded in other regions 23 24.…”
Section: Discussionsupporting
confidence: 87%
“…Within the specific context of HIV patients, these financial considerations can substantially influence their ability to avail themselves of vital medical care, procure prescribed medications and participate in routine medical assessments, thereby contributing to variations in their healthcare service avoidance behaviours. Our findings align with prior research conducted in both developed and developing countries, including instances such as Australia and Cameroon, where budgetary constraints have been identified as a hindrance to healthcare-seeking behaviours 21 22. A study conducted in Vietnam indicated that there were 73.3% of participants reported that they were able and willing to pay for HIV treatment expenditures, unlike the low individual willingness to pay rate recorded in other regions 23 24.…”
Section: Discussionsupporting
confidence: 87%
“…Financial stress from the costs of accessing ART, attending clinical appointments and pharmacy dispensing fees have been identified in other Australian research as barriers to HIV treatment, in both metropolitan and regional/rural locations (McAllister, Beardsworth, Lavie, MacRae, & Carr, 2013;Wilkinson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Our research may lead to HIV-healthcare centres initiating or expanding processes to track individuals missing scheduled appointments and perform their own contact tracing interventions to minimise the number of individuals with unknown outcomes. In addition, Australia maintains a publicly-funded healthcare model for PLHIV to access treatment, and there are mechanisms to obtain compassionate access to ART for those PLHIV who are ineligible for Medicare [ 12 ].…”
Section: Discussionmentioning
confidence: 99%